2016
DOI: 10.1021/acsami.5b12226
|View full text |Cite
|
Sign up to set email alerts
|

Creating Reversible p–n Junction on Graphene through Ferritin Adsorption

Abstract: An alternative way to construct a stable p-n junction on graphene-based field effect transistor (G-FET) through physical adsorption of ferritin (spherical protein shell) is presented. The produced p-n junction on G-FET could also operate through water-gate. Native ferritins are known to be negatively charged in wet condition; however, we found that native negatively charged ferritins became positively charged after performing electron beam (EB)-irradiation. We utilized this property to construct p-n junction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 65 publications
(95 reference statements)
2
25
0
Order By: Relevance
“…Here, we explore the use of a deionized (DI) water top gate ,, for field-effect tuning of the conductance of thick layered semiconductor FETs. This approach offers an alternative route toward efficient layered field-effect devices: instead of reducing the channel thickness to the ultimate 2D limit, the conductance of a thicker channel is switched between on and off states by a gate that supports very large electric fields at the channel surface.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we explore the use of a deionized (DI) water top gate ,, for field-effect tuning of the conductance of thick layered semiconductor FETs. This approach offers an alternative route toward efficient layered field-effect devices: instead of reducing the channel thickness to the ultimate 2D limit, the conductance of a thicker channel is switched between on and off states by a gate that supports very large electric fields at the channel surface.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the two V Dirac peaks is rare in graphene with self-organized biomolecules. Mulyana et al also reported two peaks for ferritin adsorbed on a graphene surface, but here the peak modulation was obtained by e-beam irradiation of horse spleen ferritin (Mulyana et al, 2016b). The authors argued that the observed two V Dirac peaks attributed to a certain amount of ferritins which were not completely charged by e-beam irradiation because the e-beam could not penetrate the hydrated iron oxide.…”
Section: Electrical Transport Characteristics Of Ferritin-doped Blf-fetsmentioning
confidence: 65%
“…Local potential modulation can be introduced by various means including electrostatic or chemical gating which is achieved through chemical doping with adsorption of charged molecules as a dopant (Dong et al, 2009;Farmer et al, 2009;Kulkarni et al, 2016;Mulyana et al, 2016a), or high-resolution resist materials like hydrogen silsesquioxane (HSQ) (Brenner and Murali, 2010) and SU8 (Yun et al, 2014), as a complementary dopant, or by constructing double gates below and on top of the graphene layer through electrostatic modification of gate insulator (Chiu et al, 2010) or by focused laser irradiation (Kim et al, 2013;Seo et al,2014), or strain of graphene to induce electrostatic gating, (Sun et al,2016) and as there had been several examples in the STM community (i.e., Crommie group) (Velasco et al, 2018). A major challenge is to control charge carrier density at the true nanometer scale (Kong et al, 2014;Solı ´s-Ferna ´ndez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the increased mobility could be attributed to the accumulated R6G molecules might form a protective layer on the top of the graphene surface that reduce the electron scattering, eventually increased the electron mobility. [ 19 ]…”
Section: Resultsmentioning
confidence: 99%